Progress of island health in the Maldives - Lawson Ifeanyi Eya; Imran Mohamed Adam; Muiz Ibrahim; Adriana Viola Miranda; Subbaram Kannan; Don Eliseo Lucero‐Prisno III (Wiley, 2023)
Abstract The provision of equitable healthcare on remote islands is critical in the fight to attain the sustainable development goals (SDGs). Many island countries, particularly the Small Island Developing States (SIDS), are confronted with numerous obstacles to accessing quality healthcare. Many SIDS are located in the Asia‐Pacific region, and they suffer shared challenges such as a lack of infrastructure, logistical concerns, and a shortage of health staff. As a SIDS, the Maldives has made significant progress in the health sector, when compared to its neighbours. Part of this is due to spending a large portion of the national budget on the social sector, and a well‐structured health system. Despite these accomplishments, it continues to struggle to provide equitable health care across the whole nation, especially to the small and underpopulated islands. One contributing factor is the dispersed geography. The pandemic highlighted the importance of telemedicine and its capacity to bridge the barriers to healthcare delivery, and its potential in the Maldives is huge. There is also a need to strengthen integrated health services through primary healthcare, train a larger workforce, and upgrade hospitals to be able to provide comprehensive medical services. This will limit the frequency of travel to the capital and abroad in search of better healthcare.